2009
DOI: 10.1111/j.1747-0765.2008.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Element interconnections inLotus japonicus: A systematic study of the effects of element additions on different natural variants

Abstract: Lotus japonicus was used to study the distribution and interconnections of 15 elements in plant tissues, including essential and non-essential elements: boron (B), sodium (Na), magnesium (Mg), potassium (K), calcium (Ca), manganese (Mn), iron (Fe), nickel (Ni), copper (Cu), zinc (Zn), arsenic (As), strontium (Sr), molybdenum (Mo), cadmium (Cd) and cesium (Cs). Large amounts of B and Ca accumulated in plant leaves, while Fe, Na, Ni, As and Cd tended to mainly occur in the roots, and Mo was the only element to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 68 publications
4
29
0
1
Order By: Relevance
“…Iron is not deficient in mineral soil, but due to high pH and calcareousness, it is merely available to plants because at high pH, Fe +2 ions (absorbed by plants) converted into less soluble Fe +3 oxides and hydroxides and disappear from the soil solution (Marschner 1995). Nickel and Fe have an antagonistic effect in which high concentration of Ni in the soil reduces endogenous Fe concentration and reduces its bioavailability to crops (Chen et al 2009;Ghasemi et al 2009;Nishida et al 2012). Interestingly, different authors have also confirmed that high concentration of Fe +2 suppresses Ni +2 absorption and translocation in plants (Cataldo et al 1978;Marschner 1995).…”
Section: Introductionmentioning
confidence: 84%
“…Iron is not deficient in mineral soil, but due to high pH and calcareousness, it is merely available to plants because at high pH, Fe +2 ions (absorbed by plants) converted into less soluble Fe +3 oxides and hydroxides and disappear from the soil solution (Marschner 1995). Nickel and Fe have an antagonistic effect in which high concentration of Ni in the soil reduces endogenous Fe concentration and reduces its bioavailability to crops (Chen et al 2009;Ghasemi et al 2009;Nishida et al 2012). Interestingly, different authors have also confirmed that high concentration of Fe +2 suppresses Ni +2 absorption and translocation in plants (Cataldo et al 1978;Marschner 1995).…”
Section: Introductionmentioning
confidence: 84%
“…uptake by plants has been introduced as the ionome (Hirschi 2003;Lahner et al 2003;Rea 2003;Salt 2004). After treatment with ethyl methanesulfonate of the seeds of Lotus japonicus ((Regel) K. Larsen), Chen et al (2008Chen et al ( , 2009) screened mineral uptake properties via ionome analysis, and reported a Cs accumulator without the coordinated change of other elements, indicating the possibility of varietal change specific to Cs accumulation of one species. This indicates the possibility of a physiological mechanism to regulate Cs uptake by plants.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cd significantly decreased the Fe content in shoots, but significantly increased the Fe content in roots (Gao et al 2011). Similarly, a higher Fe accumulation was detected in the roots of Lonicera japonica , Lotus japonicus (Chen et al 2009), and tomato (López-Millán et al 2009;Luo et al 2012) under Cd stress. Additional studies revealed that the significant Fe content increase under Cd stress accumulated in root apoplasts (Fodor et al 2005;Yoshihara et al 2006;Zhang et al 2000).…”
mentioning
confidence: 80%